Effectiveness of electromagnetic monitoring in studying earthquakes - Piriyev, R.H. (Geofizicheskiy Zhurnal, 2021)
Numerous researches conducted in connection with the study of earthquakes have shown that electromagnetic monitoring studies have led to some important results. From the Loma Prieta earthquake to the Guam earthquake, electromagnetic monitoring studies led to significant results. Since then, there have been numerous reports of possible elect-romagnetic precursors to earthquakes, some of which have involved frequencies covered by ELF/VLF (10—32 kHz) monitoring system Fraser-Smith et al. [1990]. Sometime later, they retrieved and started processing their ULF data. They had less reason to expect electromagnetic precursors in this latter data, because previous reports of precursory signals at frequencies below the ELF/VLF range have, with few exceptions, involved frequencies either below or predominantly below their ULF range (0.01—10 Hz) of operation. They found out that ELF/VLF data do not appear to show precursory activity, whereas ULF data contain a number of anomalous features that may prove to be earthquake precursors. The lack of observation of precursory ELF/VLF noise so close to the epicenters of several mode-rate to moderately-large earthquakes showed that ELF/VLF noise need not be a strong or obvious feature of every earthquake, as Fraser-Smith et al. [1990] reported in their paper. At present, numerous studies have been conducted in this area and researches are being improved. From my experience as a young researcher, it became clear that electromagnetic monitoring research is necessary, and that more important and significant results can be achieved if continuous research is conducted in a certain area. Thus, these studies may play a significant role in the detection of earthquake precursors.